Preserving Creation in Times of Conflict: A Biblical Response to Deforestation and Environmental Degradation in Nigeria’s War Zones - Emmanuel Olurokan Olowoyeye; Kolade Samuel Oluwasegun; Caleb Abiodun Adeleye (Institut Kristen Teologi Real Batam, 2026)
Nigeria's conflict-affected regions, particularly the Northeast, Middle Belt, and Niger Delta, have experienced severe deforestation driven by insurgency, displacement, military operations, and resource extraction. These dynamics have deepened food insecurity, accelerated biodiversity loss, and produced long-term ecological degradation across communities already burdened by violence. While environmental scholarship has documented these impacts with growing urgency, theological and eco-theological studies have insufficiently engaged the question of how biblical war legislation conceptualizes limits to environmental destruction in conflict settings. This study addresses that gap by revisiting Deuteronomy 20:19–20, examining how this ancient legal text articulates constraints on ecological harm within the context of warfare and how its ethical logic may be critically, rather than prescriptively, related to contemporary conflict-induced deforestation in Nigeria. The study employs an integrated methodological framework combining historical-critical, literary, and eco-theological approaches, further deepened by just war theory, political theology, and postcolonial critique. Findings reveal that Deuteronomy 20:19–20 functions primarily as a legal constraint on totalizing destruction, reflecting an internal tension between military necessity and resource preservation rather than a fully developed ecological ethic. Its significance for contemporary discourse lies not in direct normative transfer but in its capacity to illuminate enduring tensions between violence, governance, and environmental limitation. The study therefore reframes the passage as a dialogical resource for critical theological reflection, one that invites engagement with the moral boundaries of warfare and the sacred responsibility toward creation, without assuming direct continuity between ancient and modern contexts. Abstrak Wilayah-wilayah Nigeria yang dilanda konflik, khususnya Timur Laut, Sabuk Tengah, dan Delta Niger, telah mengalami deforestasi parah akibat pemberontakan, perpindahan penduduk, operasi militer, dan eksploitasi sumber daya alam. Dinamika-dinamika ini telah memperparah ketidakamanan pangan, mempercepat hilangnya keanekaragaman hayati, dan menghasilkan degradasi ekologis jangka panjang di tengah komunitas yang sudah terbebani oleh kekerasan. Meskipun kajian lingkungan hidup telah mendokumentasikan dampak-dampak tersebut dengan urgensi yang semakin meningkat, studi teologis dan eko-teologis belum cukup mengkaji pertanyaan tentang bagaimana perundang-undangan perang dalam Alkitab mengonseptualisasikan batasan terhadap kerusakan lingkungan dalam situasi konflik. Penelitian ini mengisi kesenjangan tersebut dengan mengkaji ulang Ulangan 20:19–20, menelaah bagaimana teks hukum kuno ini mengartikulasikan pembatasan terhadap kerusakan ekologis dalam konteks peperangan dan bagaimana logika etisnya dapat dikaitkan secara kritis, bukan preskriptif, dengan deforestasi akibat konflik kontemporer di Nigeria. Penelitian ini menggunakan kerangka metodologis terpadu yang menggabungkan pendekatan historis-kritis, sastra, dan eko-teologis, yang diperdalam lebih lanjut oleh teori perang yang adil, teologi politik, dan kritik poskolonial. Temuan penelitian mengungkapkan bahwa Ulangan 20:19–20 berfungsi terutama sebagai pembatas hukum terhadap pemusnahan total, mencerminkan ketegangan internal antara keniscayaan militer dan pelestarian sumber daya, ketimbang sebagai etika ekologis yang sepenuhnya berkembang. Signifikansinya bagi wacana kontemporer terletak bukan pada transfer normatif secara langsung, melainkan pada kemampuannya menerangi ketegangan abadi antara kekerasan, tata kelola, dan pembatasan lingkungan. Penelitian ini karenanya merumuskan ulang perikop tersebut sebagai sumber dialogis untuk refleksi teologis kritis, yang mengundang keterlibatan dengan batas-batas moral peperangan dan tanggung jawab sakral terhadap ciptaan, tanpa mengandaikan kesinambungan langsung antara konteks kuno dan modern.